2000
DOI: 10.1530/reprod/118.2.243
|View full text |Cite
|
Sign up to set email alerts
|

Difference in localization of eosinophils and mast cells in the bovine ovary

Abstract: The bovine ovary contains a considerable number of leucocytes which can be located with an antibody against the CD18 molecule. In the present study, subtyping and cell counting were carried out on histological sections stained with Sirius red for eosinophils and with toluidine blue for mast cells. The CD18(+) cells were identified immunohistologically. Eosinophils and mast cells contributed considerably to the CD18(+) pool. The number of eosinophils in the corpus luteum increased rapidly in early development t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(3 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The development of the bovine CL is accompanied by active angiogenesis, and the structure of blood vessels is retained during pregnancy (O'Shea et al 1989, Lei et al 1991, Beindorff et al 2010. Leukocytes, including monocytes/macrophages, granulocytes, and T lymphocytes, are localized to the CL in several species (Standaert et al 1991, Brannstrom et al 1994, Reibiger & Spanel-Borowski 2000. These findings suggest that the bovine CL should have a lymphatic system with essential roles in regulating the functions of its immune cells.…”
Section: Introductionmentioning
confidence: 97%
“…The development of the bovine CL is accompanied by active angiogenesis, and the structure of blood vessels is retained during pregnancy (O'Shea et al 1989, Lei et al 1991, Beindorff et al 2010. Leukocytes, including monocytes/macrophages, granulocytes, and T lymphocytes, are localized to the CL in several species (Standaert et al 1991, Brannstrom et al 1994, Reibiger & Spanel-Borowski 2000. These findings suggest that the bovine CL should have a lymphatic system with essential roles in regulating the functions of its immune cells.…”
Section: Introductionmentioning
confidence: 97%
“…Leukocytes are attracted into the ovary and influence cyclically changing structures [1–3]. Recently, we reported that the eosinophils suddenly increase in number to roughly 90% of the leukocytes in the bovine corpus luteum of early development [4]. In sheep, the eosinophils are assumed to influence the neovascularization of the corpus luteum [5].…”
Section: Introductionmentioning
confidence: 99%
“…15 Mastócitos foram extensivamente estudados em fêmeas, relacionando-os com as diversas fases do ciclo estral. 16,17,18,19 Diferentemente das fêmeas, há poucos trabalhos relacionando os mastócitos e o sistema reprodutor masculino. Gaytan et al 20 verificaram aumento na quantidade de mastócitos testiculares em ratos após tratamento neonatal com estrógeno, sem diferenças significativas na próstata e no epidídimo.…”
Section: Introductionunclassified